Book and Radio Play Silences: Medial Pauses and Reticence in 'Murke's Collected Silences' by Heinrich Böll. Issue 3 (December 2019) - Keskinen, Mikko
Abstract : This article analyses silence at the interface between print and audio media by reading and listening to Heinrich Böll's short story 'Murke's Collected Silences' ('Doktor Murkes gesammeltes Schweigen') in its book (1958) and three German-language radio play versions (1965; 1986; 1989). Reference is also made to Benjamin Gwilliam's sound art piece (2007) based on the 1986 adaptation. The Böll story thematises silence and media in various ways, and has definite countertextual aspects, in the sense of technology, textuality, and materiality of language. In the printed story, silence is either verbally named or typographically indicated, whereas the radio plays present or perform it. The comparison of the three silence-related scenes in the Murke radio plays shows considerable variation in the length and manner of pauses. The article considers the differences in receiving silence through print and audio media, and concludes that 'Murke' demonstrates, in both formats, that the medium is an integral part of the 'message', even the silent one.